A Development of Biodiversity Module Based on Socioscientific Issues and Local Potential for Department Students of IKIP PGRI Pontianak - Eka Trisianawati; Ivan Eldes Dafrita; Handi Darmawan (Indonesian Journal of Biology Education, 2019)
This study aims to investigate: (1) The feasibility of biodiversity module based on Socioscientific issues and local potential according to the expert of material and the expert of media; (2) The students learning outcomes or achievements after using the biodiversity module based on Socioscientific issues and local potential. The method used in this study is a research and development (R & D) method with Hannafin and Peck's model. The subject of this study is the third-semester students of Mathematics Education Department of IKIP PGRI Pontianak who take the General Biology lesson in the academic year 2018/2019 that consist of one class, namely Class A Afternoon. The technique of collecting data used in this study is an indirect communication technique with the data collection tool in the form of a validation questionnaire and a test to gain the data of students learning achievement. The result of this study are: (1) The biodiversity module based on Socioscientific issues and local potential that is developed and worthy to be used with the indexed percentage of 75.91%; (2) Students learning achievement after using the biodiversity module based on Socioscientific issues and local potential that is developed is increasing with the normalized gain value of 0.6 that belongs to the medium category.